Pengaruh Life Style, Social Media Marketing Dan Product Differentiation Terhadap Keputusan Pembelian Produk Mayang Collection - Nabila, Alsya; Rizal, Mohammad; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The purpose of this research is to determine and analyze the influence of lifestyle, social media marketing, and product differentiation on purchasing decisions, including the influence of lifestyle on purchasing decisions, social media marketing on purchasing decisions, and product differentiation on purchasing decisions. This thesis employs explanatory research, with a sample size of 105 respondents. The data were analyzed using multiple linear regression analysis. The results indicate that lifestyle, social media marketing, and product differentiation significantly influence purchasing decisions for Mayang Collection products. Lifestyle significantly influences purchasing decisions for Mayang Collection products, meaning that as lifestyle increases, purchasing decisions for Mayang Collection products will increase. Social media marketing significantly influences purchasing decisions for Mayang Collection products, meaning that as social media marketing increases, purchasing decisions for Mayang Collection products will increase. Product differentiation significantly influences purchasing decisions for Mayang Collection products, meaning that as product differentiation increases, purchasing decisions for Mayang Collection products will increase. Keywords: Lifestyle, Social Media Marketing, Product Differentiation, and Purchasing Decisions